Solvent-free synthesis method of 1,3-bis(benzo-1,2,3-triazolyl)propane; Advances in synthesisand complexing; Vol. 1 : Organic Chemistry Section - Marchenko R. D. Roman Dmitrievich (2017, 2017)
Title screen